2023
DOI: 10.1519/jsc.0000000000003018
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for Professional Mixed Martial Arts Training With Pacing Strategy and Technical-Tactical Actions by Rounds

Abstract: Suggestions for professional mixed martial arts training with pacing strategy and technical-tactical actions by rounds. J Strength Cond Res 37(6): 1306-1314, 2023-This study compared the pacing strategy and motor actions used in mixed martial arts combats ending by knockout/technical knockout (KO/TKO) or submission. All of the sample bouts ended in KO/TKO and consisted of 1,564 rounds of 678 bouts. The bouts were separated by round (R) of bouts ending (ER) in the first round (n 5 192), first (1R 3 2ER) and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
3
26
0
5
Order By: Relevance
“…Considering all fight outcomes by year between 2008 and 2017, the following were observed: total fights: 173,288; submission: 67,134 (0.39); decision: 41,985 (0.24); and (T) KOs: 61,395 (0.35). In contrast, another study showed the decision as the main fight outcome reported [ 12 ], and this is in line with the following studies: in 174 female MMA fights, 72.4% ( n = 126) fight outcomes were by the decision of the judges, 11.4% ( n = 20) by submission, and 16% ( n = 28) by KO or TKO [ 6 ]; the results of an MMA study that considered 304 bouts between male fighters demonstrated ( n = 210) fight outcomes by decision, ( n = 40) fight outcomes by submission, and ( n = 54) fight outcomes by KO/TKO [ 14 ]. However, different results have been observed in a previous study, which demonstrated that the majority of amateur male fights ended in KO (57.7%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering all fight outcomes by year between 2008 and 2017, the following were observed: total fights: 173,288; submission: 67,134 (0.39); decision: 41,985 (0.24); and (T) KOs: 61,395 (0.35). In contrast, another study showed the decision as the main fight outcome reported [ 12 ], and this is in line with the following studies: in 174 female MMA fights, 72.4% ( n = 126) fight outcomes were by the decision of the judges, 11.4% ( n = 20) by submission, and 16% ( n = 28) by KO or TKO [ 6 ]; the results of an MMA study that considered 304 bouts between male fighters demonstrated ( n = 210) fight outcomes by decision, ( n = 40) fight outcomes by submission, and ( n = 54) fight outcomes by KO/TKO [ 14 ]. However, different results have been observed in a previous study, which demonstrated that the majority of amateur male fights ended in KO (57.7%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that the ability to perform the fight on the ground is an efficient strategy; that is, grappling submission proved to be a determinant style in the Ultimate Full Contact. This is because the frequencies of the fight outcomes are related to fight skills or styles [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants had previous experience (>2 years) with official judo events (range level: local to national), rules and procedures (International Judo Federation (IJF), 2018). No modifications were made in the judo training (range frequency: two to five times/week, range time: three to 12 h/week) nutritional or hydration status of participants, following preceding protocols (Antonietto et al, 2019). There are no ethical problems in investigating data of public events, as disposed by prior protocols (Sterkowicz-Przybycien et al, 2017).…”
Section: Samplementioning
confidence: 99%